Comparison of the Short-Term Efficacy of Physical Therapy in Subacromial Impingement Syndrome Patients with Stage I and II Magnetic Resonance Imaging Findings - Aral HAKGÜDER; Nurettin TAŞTEKİN and Murat BİRTANE and Kaan UZUNCA and Coşkun ZATERİ and Necdet SÜT3 (Archives of Rheumatology, 2011)
Objectives: In this study, we compared the efficacy of a combined physical therapy program between stage I and II subacromial impingement syndrome patients. Patients and methods: Forty-three patients with subacromial impingement syndrome assessed as stage I and II according to the magnetic resonance imaging (MRI) findings were included in the study. Constantʼs and University of California Los Angeles Shoulder Scales were used to evaluate pain and function. Pain levels at rest, during motion and while asleep were also scored by visual analog scale before treatment, after treatment and at one month after treatment. Improvements within and between the groups were assessed. A physical therapy program consisting of ultrasound, superficial heat therapy and transcutaneous electrical nerve stimulation modalities combined with an appropriate exercise program was applied to both groups during half monthly sessions. Results: The between-groups comparisons performed after treatment and during follow-up revealed no significant difference in terms of the outcome measures assessed. Conclusion: Stage II patients responded to the physical therapy program as well as patients with stage I MRI findings.